O trabalho: componente esquecida no documento de estratégia de crescimento e de redução da pobreza nos Comores - Abdallah Nouroudine (Universidade do Porto, 2008)
Classical development approaches neglect work, in general, and its conditions in particular. From the Structural Adjustment Programs to the Strategies for Growth and for Poverty Reduction, we observe a relative integration of the plurality of life dimensions. Nevertheless, work is not always really considered. This compromises the possibilities of transforming strategies and goals for development in activities and work for development, in order to simultaneously transform people´s work conditions and life conditions. A better consideration of work and of human activities would favour local populations´ appropriation by of the transformation processes inherent to development.